DERMA: A Melanoma Diagnosis Platform Based on Collaborative Multilabel Analog Reasoning - Ruben Nicolas; Albert Fornells; Elisabet Golobardes; Guiomar Corral; Susana Puig; Josep Malvehy (The Scientific World Journal)
The number of melanoma cancer-related death has increased over the last few years due to the new solar habits. Early diagnosis has become the best prevention method. This work presents a melanoma diagnosis architecture based on the collaboration of several multilabel case-based reasoning subsystems called DERMA. The system has to face up several challenges that include data characterization, pattern matching, reliable diagnosis, and self-explanation capabilities. Experiments using subsystems specialized in confocal and dermoscopy images have provided promising results for helping experts to assess melanoma diagnosis.